Market share analysis: international direct offer to and from Santiago de Chileâ€™s International Airport Arturo Merino Benitez (2017-2019) - Ribadeneira-Páez, María Gracia; Vega-Pérez, Oswaldo Sebastián; Cruz-Pierard, Jonathan Luis (Dominio de las Ciencias, 2021)
This research work has a qualitative, exploratory and descriptive approach of bibliographic type that has for objective determine the market share generated by commercial airlines of passenger transport that operate direct international routes to and from Arturo Merino Benitez International Airport of Santiago de Chile during the period 2017-2019, as well as to dimension the size of airlines' offer, identify the market leader and observer its behavior